Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1128/aac.01707-09
|View full text |Cite
|
Sign up to set email alerts
|

Colistin Dosing and Nephrotoxicity in a Large Community Teaching Hospital

Abstract: Thirty adult patients who received intravenous colistin (5.1 ؎ 2.4 mg/kg/day) were reviewed to evaluate dosing with respect to nephrotoxicity, which occurred in 10 (33%) patients within the first 5 days of treatment. Excessive colistin dosing was frequent (47%), often (71%) resulted from the use of actual body weight in obese patients, and was associated with higher rates of nephrotoxicity (80% versus 30%, P ‫؍‬ 0.019).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
142
2
10

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(174 citation statements)
references
References 19 publications
15
142
2
10
Order By: Relevance
“…An association between the use of diuretics and the development of AKI has been shown in previous studies (18,27). Similarly, in our study, concomitant usage of loop diuretics and higher dose colistin were identified as independent risk factors for AKI development.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…An association between the use of diuretics and the development of AKI has been shown in previous studies (18,27). Similarly, in our study, concomitant usage of loop diuretics and higher dose colistin were identified as independent risk factors for AKI development.…”
Section: Discussionsupporting
confidence: 62%
“…Although colistin has been used for more than 50 years, the levels of the most effective and least toxic doses are still unclear (18). One reason may be the different dosage recommendations included with various forms of colistin products.…”
Section: Discussionmentioning
confidence: 99%
“…Nephrotoxicity was the only ADR observed in UTI patients treated with colistin. Nephrotoxicity as defined earlier (DeRyke et al, 2010) was manifested in 29/80 (36.3%) patients. The mean time for onset of elevation in serum creatinine was 5.48 ± 3.41 days (mean 5 days, median 1-18 days).…”
Section: Resultsmentioning
confidence: 76%
“…Renal function tests, including serum urea and serum creatinine (SCR) levels were measured prior to starting colistin and continuously monitored throughout the duration of colistin therapy and also on first revisit where possible. Nephrotoxicity was defined as at least two consecutive SCR measurements with an increase of 0.5 mg/dl from baseline at least 24 hours apart after two or more days of colistin therapy (DeRyke et al, 2010). In patients with pre-existing renal dysfunction, renal failure was defined as an increase of SCR level ≥ 50 % compared with baseline value.…”
Section: Methodsmentioning
confidence: 99%
“…Age, severity of the underlying disease, co-existence of septic shock, use of other nephrotoxic agents, time of exposure to colistin and cumulative dose are reported to be associated with colistin nephrotoxicity. [6,20,29] In the present study, colistin-related nephrotoxicity occurred at a rate of 19.2% and on median day 6. No correlation was found between exposure time or cumulative time and nephrotoxicity.…”
Section: Discussionmentioning
confidence: 95%